Optimal distribution of linear control intensity over the frequency range. - Corbi, Ottavia
In this paper, a control strategy for structural systems is proposed and developed in the frequency domain. The algorithm is substantially based on a linear derivative feedback and a convolution of the control parameter, whose distribution in the frequency field is chosen in such a manner as to comply with the requirements of an ad hoc formulated constrained optimum problem, with the response data monitored until the instant of control action application. Some numerical testing is carried out by referring to given recorded accelerograms, showing a good performance of the proposed approach.
Keywords: Harmonic control; Frequency distribution; Low energy demand